La–Ce isotope measurements by multicollector-ICPMS. Issue 12 (23rd October 2017) - Schnabel, Christiane; Münker, Carsten; Strub, Erik
Abstract : Introduction of a new analytical protocol for Ce isotope and La–Ce isotope dilution measurements by MC-ICPMS and initiation of a new Ce reference material (Cologne-AMES). Abstract : The 138 La– 138 Ce decay system (half-life 1.02 × 10 11 years) is a potentially highly useful tool to unravel information about the timing of geological processes and about the interaction of geological reservoirs on earth, complementing information from the more popular 147 Sm– 143 Nd and 176 Lu– 176 Hf isotope systems. Previously published analytical protocols were limited to TIMS. Here we present for the first time an analytical protocol that employs MC-ICPMS, with an improved precision and sensitivity. To perform sufficiently accurate La–Ce measurements, an efficient ion-chromatographic procedure is required to separate Ce from the other rare earth elements (REE) and Ba quantitatively. This study presents an improved ion-chromatographic procedure that separates La and Ce from rock samples using a three-step column separation. After REE separation by cation exchange, Ce is separated employing an Ln Spec column and selective oxidation. In the last step, a cation clean-up chemistry is performed to remove all remaining interferences. Our MC-ICPMS measurement protocol includes all stable Ce isotopes ( 136 Ce, 138 Ce, 140 Ce and 142 Ce), by employing a 10 10 ohm amplifier for the most abundant isotope 140 Ce. An external reproducibility of ±0.25 ε -units (2 r.s.d) has been routinely achieved for 138 Ce measurements for as little as 150–600 ng Ce, depending on the sample–skimmer cone combinations being used. Because the traditionally used JMC-304 Ce reference material is not commercially available anymore, a new reference material was prepared from AMES laboratory Ce metal (Cologne-AMES). In order to compare the new material with the previously reported isotopic composition of AMES material prepared at Mainz (Mainz-AMES), Cologne-AMES and JMC-304 were measured relative to each other in the same analytical session, demonstrating isotope heterogeneity between the two AMES and different JMC-304 batches used in the literature. To enable sufficiently precise age correction of radiogenic 138 Ce and to perform isochron dating, a protocol was developed where La and Ce concentrations are determined by isotope dilution (ID), using an isotope tracer enriched in 138 La and 142 Ce. The new protocols were applied to determine the variations of Ce isotope compositions and La–Ce concentrations of certified geochemical reference materials (CRMs): BCR-2, BCR-1, BHVO-2, JR-1, JA-2, JB-3, JG-1, JR-1, JB-1b, AGV-1 and one in-house La Palma standard.